PRELIMINARY REPORT ON TWO TRIASSIC DICYNODONTS FROM ZAMBIA - Crozier, E. A. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1970)
The purpose of this communication is to establish the presence of a species of Stahleckeriid, hitherto known only from India, in the Zambian Triassic N'tawere Formation and to establish the new specific name of the Kannemeyeria specimen also recorded from the same locality.